Efforts to Detect and Handle of Interrupted Ectopic Pregnancy - Farida Ariyani; Yulia Arifin (Global Health Science Group, 2022)
Ectopic pregnancy is a complication due to fetal growth and implantation not in the endometrium in the uterine cavity. This will be heavy if the condition becomes disrupted and pregnancy has abortion. The incidence of ectopic pregnancy is disturbed about 1% -2% of all pregnancies. However, abortion from ectopic pregnancy causes emergencies for the mother even to experience death. Disrupted ectopic pregnancy is the main cause of death in the first trimester of pregnancy. This research was conducted on 3 pregnant women who experienced a disturbed ectopic pregnancy. To detect risk factors and management of the event of disturbed ectopic pregnancy in pregnant women. This type of research is descriptive with a case study approach. Results: The results of this study were found that, first pregnancy in old age, respondents had a history of obstetric gravida 1-2, had a history of cysts, using IUD contraception, Caesaria section labour. The patient's condition can end well, although in an effort to make referral decisions experiencing obstacles from the family at first. Conclusion: Appropriate detection and treatment of emergency conditions can reduce unexpected prognosis from the complications experienced by the patient.